A Systematic Literature Review on Green Employee Empowerment and Green Human Resource Management - Karki, Surendra; Bhandari, Mohan (Journal of Interdisciplinary Studies, 2025)
This study aims to systematically review and synthesize the existing literature on Green Employee Empowerment (GEE) within the context of Green Human Resource Management (GHRM). A Systematic Literature Review (SLR) was conducted following the PRISMA framework. Data were collected from the Dimensions database using the search strings “Green,” “Employee,” “Empowerment,” and “Human Resource Management,” focusing on journal articles published between 2016 and 2025. A total of 936 articles were initially identified, and after rigorous screening and eligibility assessment, 59 studies were included for synthesis. Thematic analysis was employed to extract patterns and conceptual relationships. The review identified six major themes: (a) GHRM practices and organizational outcomes, (b) employee empowerment and pro-environmental behavior, (c) leadership and psychological empowerment, (d) training and knowledge management, (e) work-life balance and employee retention, and (f) innovation, creativity, and green performance. Each theme demonstrated that empowerment fosters environmental responsibility, innovation, and sustainable organizational behavior through supportive HR systems and participatory cultures. The findings suggest that GEE serves as a strategic enabler of sustainability by enhancing employee engagement, green innovation, and environmental citizenship. Organizations should integrate empowerment-based HR practices and leadership support to strengthen sustainable performance and green transformation.